Hadith #2001 - Jami' al-Tirmidhi - Abd bin Hameed bin Nasr عبد بن حميد بن نصر; Abu Bakr As-Siddique; Abu Salma al-Kundi أبو سلمة الكندي - عثمان بن مقسم; Farqad bin Y'aqub al-Sabkhi فرقد بن يعقوب السبخي; Murrah bin Shrahayl al-Hamdani مرة بن شراحيل الهمداني - الطيب - الخير; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Jami' al-Tirmidhi)
“The Messenger of Allah said: ‘Whoever has a speck of pride (arrogance) in his heart, shall not be admitted into Paradise. And whoever has a speck of faith in his heart, shall not be admitted in to the Fire.'” He said: “So a man said to him: ‘I like for my clothes to be nice, and my sandals to be nice?’ So he said: ‘Indeed Allah loves beauty. But pride is refusing the truth and belittling the people.'”
Grade:

Hadith #2829 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; Murrah bin Shrahayl al-Hamdani مرة بن شراحيل الهمداني - الطيب - الخير; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“I used to twist the garlands for the sacrificial animal of the Prophet (ﷺ), and his sacrificial animal would be garlanded and sent (to Makkah), and he would stay (in Al-Madinah) without avoiding any of the things that the one in Ihram avoids.”
Grade: